2018
DOI: 10.5194/angeo-36-205-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation and cross-wavelet analyses of the solar wind IMF Bz and auroral electrojet index AE coupling during HILDCAAs

Abstract: Abstract. Solar-wind-geomagnetic activity coupling during high-intensity long-duration continuous AE (auroral electrojet) activities (HILDCAAs) is investigated in this work. The 1 min AE index and the interplanetary magnetic field (IMF) B z component in the geocentric solar magnetospheric (GSM) coordinate system were used in this study. We have considered HILDCAA events occurring between 1995 and 2011. Cross-wavelet and cross-correlation analyses results show that the coupling between the solar wind and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Hajra et al (2014) have shown the main process of solar wind energy dissipation in the magnetosphere during HILDCAA is by Joule heating in the auroral region, which is responsible for 67 % of the input energy. It was seen that the coupling between solar wind and the magnetosphere during these events occurs mainly in periods ≤ 8 h (Souza et al, 2018). Similar periods were observed in most energetic periods in the AE index and B z IMF component.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Hajra et al (2014) have shown the main process of solar wind energy dissipation in the magnetosphere during HILDCAA is by Joule heating in the auroral region, which is responsible for 67 % of the input energy. It was seen that the coupling between solar wind and the magnetosphere during these events occurs mainly in periods ≤ 8 h (Souza et al, 2018). Similar periods were observed in most energetic periods in the AE index and B z IMF component.…”
Section: Introductionsupporting
confidence: 70%
“…Non-stationary time series can be analyzed by wavelet transform (WT), a powerful mathematical tool that is able to show the temporal variability of the power spectral density (Morettin, 1992). Wavelet functions ψ (t) are generated by a simple function called wavelet mother, shown in Equation 1, which suffers expansion ψ (t) → ψ (2t) and translations ψ (t) → ψ (t + 1) in time, giving rise to those wavelet functions well known as wavelet daughters (Torrence and Compo, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During all HILDCAA categories, the periodicities of the most energetic short-term power fluctuations are found to lie within the range of 0.5-3 hr. This lies within the range (<8 hr) where the solar-wind-magnetospheric coupling occurs during HILDCAA (de Souza et al, 2018). However, in majority of cases (~68% of 72 CIR HILDCAAs,~75% of 12 ICME HILCCAAs, and 56% of 29 nonstorm HILDCAAs), the most energetic periods are centered around 1.5-3 hr.…”
Section: 1029/2018sw001879mentioning
confidence: 75%
“…The CIRs are characterized by compressed plasma and magnetic field regions. These are known to be geoeffective causing weak to moderate geomagnetic storms, and intense, long-duration auroral activities at the Earth (Tsurutani & Gonzalez 1987;Tsurutani et al 2006;Hajra et al 2013Hajra et al , 2014aHajra et al ,c,b, 2015aHajra et al ,b, 2017aSouza et al 2016Souza et al , 2018Mendes et al 2017;Guarnieri et al 2018;Hajra & Tsurutani 2018a). They result from magnetic reconnection (Dungey 1961) between the southward component of CIR magnetic fields and the Earth's dayside magnetopause fields.…”
mentioning
confidence: 99%